Effect of Pleurotus ostreatus White-rot fungi on Chemical Properties of Beech (Fagus orientalis) Wood Chips - Ateş, Saim; Akyildiz, Didem; Olgun, Çağrı (Kastamonu University, 2016)
Defibration is one of the most energy spent stage in pulp and fiberboard production. Today’s different methods are available for reducing energy needs at this stage. Fungi usage is an important method for this purpose in recent decades. In this study, beech chips ( Fagus orientalis ), which is the most widely used in the Turkish fiberboard industry, are pretreated with edible Pleurotus ostreatus white rot fungi and investigated the effects of the chemical content of the chips. Consequently, totally 7727.6 gr P. ostreatus mushroom is obtained and the lignin content of wood chips is dramatically decreased day by day. It was observed that lignin content of wood chips decreased by 22.03% at 72th day after starting of fungi to emerge. Accordingly this results, it will be potentially saved the mechanical fibrillation energy, because dissolving the desired amount of lignin during fiberizing is reduced.